1962
DOI: 10.1126/science.137.3533.835
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for Human Cancer Viruses

Abstract: ference, and the first steps were taken at that conference to clear channels for radio astronomy. The very important band of frequencies near the hydrogen line (1400 to 1427 Mcy/sec) was cleared, as a result of almost complete agreement. Various other frequency bands were given less protection, generally by allowing radio astronomy to share the band with other users. Although the results of the 1959 conference obviously fall short of all that radio astronomers hope for, the con-ference represents to scientists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
69
0
2

Year Published

1963
1963
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(72 citation statements)
references
References 9 publications
1
69
0
2
Order By: Relevance
“…It is not possible to review all of the literature on this subject here but there are a number of reviews that cover this subject (Gross, 1966;Gallimore et al, 1984;Williams et al, 1995). From the in vivo studies in the 1960's it soon became clear that there were indeed tumorigenic (Huebner et al, 1962;Trentin et al, 1962, Girardi et al, 1964Pereira et al, 1965) and nontumorigenic adenoviruses (Trentin et al, , 1968. As well as Ad serotype, adenovirus induced tumorigenicity was found to be dependent on virus dose , host genetic constitution (Yabe et al, 1964, Yohn et al, 1965Allison et al, 1967), age at inoculation and the host's immune status (Yohn et al, 1965;Allison et al, 1967).…”
mentioning
confidence: 99%
“…It is not possible to review all of the literature on this subject here but there are a number of reviews that cover this subject (Gross, 1966;Gallimore et al, 1984;Williams et al, 1995). From the in vivo studies in the 1960's it soon became clear that there were indeed tumorigenic (Huebner et al, 1962;Trentin et al, 1962, Girardi et al, 1964Pereira et al, 1965) and nontumorigenic adenoviruses (Trentin et al, , 1968. As well as Ad serotype, adenovirus induced tumorigenicity was found to be dependent on virus dose , host genetic constitution (Yabe et al, 1964, Yohn et al, 1965Allison et al, 1967), age at inoculation and the host's immune status (Yohn et al, 1965;Allison et al, 1967).…”
mentioning
confidence: 99%
“…Their transforming and oncogenic properties have been traditionally ascribed to functions in early region 1 (E1) which encodes the classical Ad E1A and E1B oncoproteins (reviewed in Nevins and Vogt, 1996). Although subgroup D Ads are non-oncogenic in hamsters (Trentin et al, 1962), subgroup D Ad9 elicits exclusively estrogen-dependent mammary tumors in female rats following subcutaneous or intraperitoneal injection (Javier et al, 1991;Javier and Shenk, 1996). Besides its unique oncogenicity, Ad9 is unusual among Ads in requiring viral functions located outside of the E1 region for tumor induction (Javier et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…With few exceptions (Byrd et al, 1982;Fallaux et al, 1996Fallaux et al, , 1998Gallimore et al, 1986;Graham et al, 1977;Schiedner et al, 2000;van den Heuvel et al, 1992;Whittaker et al, 1984), attempts to transform primary human cells in culture by using different types of adenovirus/subgenomic DNA fragments have turned out to be unsuccessful or extremely inefficient, whereas rodent cells can be efficiently transformed (reviewed by Branton et al, 1985;Endter & Dobner, 2004;Graham, 1984;Graham et al, 1984). As it has been suggested that lagomorphs and rodents form a monophyletic group (glires) and are therefore closely related (Fig.…”
mentioning
confidence: 99%
“…Since the initial description of adenovirus type 12 (Ad12) inducing tumorigenicity in newborn rodents (Trentin et al, 1962) most of the viral genes involved in adenovirus transformation are now known, yet it still remains unclear as to why human adenoviral gene products are highly oncogenic in rodent, but not in human primary cells. With few exceptions (Byrd et al, 1982;Fallaux et al, 1996Fallaux et al, , 1998Gallimore et al, 1986;Graham et al, 1977;Schiedner et al, 2000;van den Heuvel et al, 1992;Whittaker et al, 1984), attempts to transform primary human cells in culture by using different types of adenovirus/subgenomic DNA fragments have turned out to be unsuccessful or extremely inefficient, whereas rodent cells can be efficiently transformed (reviewed by Branton et al, 1985;Endter & Dobner, 2004;Graham, 1984;Graham et al, 1984).…”
mentioning
confidence: 99%